AIRLINE COMPANY LIABILITY FOR LUGGAGE IN LOST OR DAMAGED AIRLINE - Sari, Ayunda Novita; Rijadi, Prof. Dr. Prasetijo (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
Since Indonesia has a diverse geological and territorial landscape, air transportation is preferred by certain community groups. This research study aims to examine legal protection for the loss or damage of passengers’ luggage on airplanes. The research employs a normative juridical approach, with data collected through a library study and analyzed qualitatively. As air transportation, particularly airplanes, continues to develop, many airline companies—both domestic and international—have experienced significant growth due to the increasing preference for air travel among Indonesians, as it is faster and more efficient. However, this growth must be accompanied by a high standard of service from airline companies, especially regarding baggage handling. In cases of lost baggage, lost baggage contents, or destruction of checked baggage, passengers are entitled to compensation of IDR 200,000 per kilogram, with a maximum of IDR 4,000,000 per passenger. Compensation for damaged checked baggage is determined based on the type, shape, and brand of the item.